A new method for exploiting mine geothermal energy by using functional cemented paste backfill material for phase change heat storage: Design and experimental study. (October 2022) - Liu, Hengfeng; Rodriguez-Dono, Alfonso; Zhang, Jixiong; Zhou, Nan; Wang, Yanjun; Sun, Qiang; Zhang, Luobin
Abstract: The research on mine geothermal energy exploitation has attracted global interest for many years. This paper proposes an innovative new method for geothermal-coal synergetic mining (GE-COSM) to expand the valorization of coal-based solid waste (C-BSW), reduce the environmental damage caused by coal utilization, and achieve a low-carbon transformation of the energy structure. A functional cemented paste backfill material (F-CBM) utilizing C-BSW for phase change heat storage was invented through orthogonal testing. This study obtained the main factors influencing raw material proportions on F-CBM working properties. Moreover, the optimal ratio of F-CBM raw materials was determined. F-CBM prepared with the optimal ratio showed improved working properties: the thermal conductivity (TC) and specific heat capacity (SHC) were increased by 75.70 % and 111.90 %, respectively, and the highest latent heat value was 17.37 J/g. The F-CBM's strength loss mechanism was discussed in terms of its mesostructure. In addition, it is shown that the backfilling layer formed by F-CBM in the goaf act as a thermal insulation and a phase change heat storage layer. Finally, the mine design principles of GE-COSM at different stages are summarized. These findings provide a reference for the application of F-CBM in engineering practice, and lay the groundwork for exploiting the mine geothermal energy. Graphical abstract: Unlabelled Image Highlights: Proposed a phase change heat storage for geothermal–coal synergetic mining method. The main factors affecting the working properties of the F-CBM were identified. The aperture of F-CBM was concentrated in the more harmful pores at 810.84 nm. F-CBM prepared with the optimal ratio showed superior heat storage properties. F-CBM acted as thermal insulation and a phase change heat storage layer.